Real-World Analysis of Switching Patients with Schizophrenia from Oral Risperidone or Oral Paliperidone to Once-Monthly Paliperidone Palmitate - Patel, Charmi (Drugs Real World Outcomes, 2019)
PURPOSE: Reducing the dosing frequency of antipsychotics (APs) with long-acting injectables (LAIs) such as once-monthly paliperidone palmitate (PP1M) can improve adherence and clinical outcomes for schizophrenia patients. This US study compared physical and psychiatric comorbidity-related outcomes, AP adherence, healthcare resource utilization (HRU), and costs pre- and post-transition to PP1M among schizophrenia patients treated with oral risperidone/paliperidone pre-PP1M transition. METHODS: Health insurance claims from the IQVIA™ PharMetrics Plus database (01/01/2012–07/31/2018) were used to identify adults with ≥ 2 schizophrenia diagnoses, ≥ 1 claim for PP1M, and ≥ 30 days of treatment with oral risperidone/paliperidone in the 60 days before the first PP1M claim (i.e., the index date). Comorbidity-related outcomes, adherence to APs (measured via the proportion of days covered [PDC]), all-cause per-patient-per-month (PPPM) HRU, and all-cause PPPM medical, pharmacy, and total costs (i.e., sum of medical and pharmacy costs) during the 6-month periods pre- and post-transition to PP1M were compared using generalized estimating equation models adjusted for repeated measurements. Analyses were replicated in the subset of patients with ≥ 1 all-cause inpatient stay pre-PP1M transition. FINDINGS: Among 427 schizophrenia patients transitioning from oral risperidone/paliperidone to PP1M, the mean age was 41.1 years and 37.9% were female. Following the PP1M transition, patients were less likely to have claims with a diagnosis for psychoses (odds ratio [OR] 0.41; P < 0.001), hypertension (OR 0.80; P = 0.011), depression (OR 0.70; P < 0.001), drug abuse (OR 0.60; P < 0.001), substance-related and addictive disorders (OR 0.73; P = 0.003), bipolar and related disorders (OR 0.59; P < 0.001), sleep-wake disorders (OR 0.68; P = 0.017), anxiety disorders (OR 0.78; P = 0.034), and other conditions that may require a focus of clinical attention (OR 0.58; P < 0.001). Mean PDC by APs was higher post-PP1M (mean = 0.81) versus pre-PP1M (mean = 0.68) transition. Post-PP1M, patients were less likely to have an all-cause emergency room visit (OR 0.51; P < 0.001) or inpatient stay (OR 0.39; P < 0.001) compared to pre-PP1M. All-cause total healthcare costs remained similar post- versus pre-transition to PP1M (mean monthly cost difference [MMCD] = $228; P = 0.260). Pharmacy costs increased post-PP1M (MMCD = $960; P < 0.001), but were offset by decreasing medical costs (MMCD = − $732; P < 0.001), largely driven by lower costs related to inpatient stays (MMCD = − $695; P < 0.001) and emergency room visits (MMCD = − $63; P < 0.001). For patients with ≥ 1 all-cause inpatient stay pre-PP1M transition (N = 177), a more pronounced improvement in comorbidity-related outcomes, a more pronounced reduction in HRU, and a reduction in total healthcare costs (MMCD = − $1308; P < 0.001) were observed post-transition to PP1M. IMPLICATIONS: Among schizophrenia patients in the US, transitioning to PP1M following oral risperidone/paliperidone treatment was associated with improved comorbidity-related outcomes, higher adherence, and a reduction in HRU, while remaining cost neutral. Furthermore, patients with ≥ 1 all-cause inpatient stay pre-PP1M transition had significantly lower total healthcare costs post-PP1M transition.